An analysis of how Zimbabwe’s international legal obligation to achieve the realisation of the right of access to adequate housing, can be enforced in domestic courts as a constitutional right, notwithstanding the absence of a specific constitutional right of every person to have access to adequate housing - Mavedzenge, Justice Alfred (Department of Public Law, 2018)
The Constitution of Zimbabwe of 2013 does not expressly guarantee every person a right to have access to adequate housing. However, the Government of Zimbabwe has an international legal obligation to achieve the progressive realisation of the right to have access to adequate housing by everyone in the country. This obligation is derived from art 11 (1) of the International Covenant on Economic, Social and Cultural Rights (ICESCR). Zimbabwe is a dualist state and therefore, this obligation is not directly or automatically enforceable as municipal law in Zimbabwe. It can be enforced in domestic courts only if it has been enacted into legislation or if it is entrenched as a constitutional obligation. The absence of a specific constitutional right, guaranteed for everyone to have access to adequate housing, thus raises the concern that the government may not be held accountable, in the domestic courts, to comply with its international legal obligation to ensure that everyone enjoys access to adequate housing. There is a national housing crisis in Zimbabwe that is characterised by an acute shortage of adequate housing, mass forced evictions and unfair discrimination in the allocation of housing facilities by government. There is therefore an existing need to compel government to comply with and fulfil its international legal obligations relating to the right of every person to have access to adequate housing. In the absence of an explicit constitutional guarantee of such a right, it is necessary to find alternative constitutional rights which citizens and individuals in Zimbabwe can rely on to compel Government to comply with and fulfil its international legal obligations that arise from art 11 (1) of the ICESCR. The Constitution of Zimbabwe expressly guarantees for everyone the following rights; the fundamental freedom from arbitrary evictions, the right to life, the right to equality and the children’s right to shelter. The scope of each of these rights can be interpreted broadly to include some of the duties that ordinarily arise from the right to have access to adequate housing. Therefore, these rights can be applied together to enforce the international legal duty of the state to ensure the progressive realisation of the right to have access to adequate housing by everyone in Zimbabwe.